2016
DOI: 10.1021/acscatal.6b02666
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Nature of Active Species of Nickel Phosphide Catalysts in High-Performance Electrochemical Overall Water Splitting

Abstract: A systematic structural elucidation of the near-surface active species of the two remarkably active nickel phosphides Ni12P5 and Ni2P on the basis of extensive analytical, microscopic, and spectroscopic investigations is reported. The latter can serve as complementary efficient electrocatalysts in the hydrogen (HER) versus oxygen evolution reaction (OER) in alkaline media. In the OER Ni12P5 shows enhanced performance over Ni2P due to the higher concentration of nickel in this phase, which enables the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
257
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 376 publications
(275 citation statements)
references
References 57 publications
18
257
0
Order By: Relevance
“…[28] Although a + 2oxidation state of Ni was revealed by XPS of recovered 2I (Figure S18), in situ electron paramagnetic resonance (EPR) studies detected Ni 0 as the active catalyst and oxidation of Ni 0 was transpired by the surface passivation of the catalyst in air (see below). PXRD, TEM, EDX, and XPS studies of recovered 2I after 6days of continuous photocatalytic H 2 evolution revealed the formation of amorphous Ni(OH) 2 on sg-CN (Figure S15-S18).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[28] Although a + 2oxidation state of Ni was revealed by XPS of recovered 2I (Figure S18), in situ electron paramagnetic resonance (EPR) studies detected Ni 0 as the active catalyst and oxidation of Ni 0 was transpired by the surface passivation of the catalyst in air (see below). PXRD, TEM, EDX, and XPS studies of recovered 2I after 6days of continuous photocatalytic H 2 evolution revealed the formation of amorphous Ni(OH) 2 on sg-CN (Figure S15-S18).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Highly efficient water electrolysis generally requires high-performance electrocatalysts with low overpotential, fast kinetics, and high stability. [9][10][11] Recently, transition-metal hydroxides, [7,12] phosphides, [8,[13][14][15][16] nitrides, [17,18] and chalcogenides [19][20][21][22] have been investigated as promising candidates for bifunctional electrocatalysts. [7,8] The search for earth-abundant, lowcost HER and OER electrocatalysts that are robust, have high activity and stability has triggered numerous efforts to replace noble metal-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…‐ Especially, as a typical representative of transition metal phosphides, Ni 2 P has been extensively investigated due to its strong catalytic activities . Driess and co‐workers studied the near‐surface active species of nickel phosphides, and demonstrated that the materials can be used as high‐performance electrocatalysts for OER and HER . Hu and co‐workers reported a bifunctional catalyst of Ni 2 P nanoparticles with excellent electrochemical activity for OER and HER .…”
Section: Introductionmentioning
confidence: 99%